CELESTIAL BODIES ON THE OB UGRIAN RITUAL ARTIFACTS (BASED ON ARCHAEOLOGICAL AND ETHNOGRAPHIC SOURCES OF THE 2ND MILLENNIUM AD) - A. V. Baulo; А. В. Бауло (Archaeology, Ethnology & Anthropology of Eurasia, 2018)
This study explores the religious role of celestial bodies depicted on Ob Ugrian ritual artifacts from several Russian museums, with reference to ethnographic, folkloric, and artistic sources. While neither the sun nor the moon play a major role in Ugrian religion, they are personifi ed and feature in legends and myths. Khanty and Mansi rites refer to lunar phases (new moon) and the position of the sun. Solar signs are mostly present on ritual artifacts relating to the Celestial Horseman cult, possibly derived from early cosmogonic ideas. In western Siberia, the symbols of the sun and the moon appear no earlier than AD 800. In the 10th–12th centuries, such artifacts were cast in the eastern Ural. The 13th–14th-century silver plaques from western Siberia, showing a falconer, evidence the Vogul (Mansi) migration from western Ural to their current place of residence. The scene featuring a falconer surrounded by animals, the sun, and the moon is still being represented on cloth paraphernalia of Mir-Susne-Khum, the Ob Ugrian cultural hero. Solar signs have been used by the Mansi and Khanty to decorate the sacrifi cial offerings to the goddess Kaltas, the gables of ritual barns, and burial structures. Also, they stood for signatures on documents. Статья посвящена изображениям небесных светил на сакральных атрибутах обских угров, а также их роли в верованиях и обрядах. Привлечены археологические, этнографические, фольклорные и изобразительные источники II тыс. н.э., а также материалы фондов ряда музеев России. Отмечено, что в мировоззрении обских угров солнце и месяц занимают незначительное место, тем не менее они персонифицированы и являются персонажами преданий и мифов. При организации обрядов ханты и манси учитывают фазы луны (новолуние) и движение солнца. На священных атрибутах обских угров солярные знаки встречаются в основном на предметах, относящихся к культу Небесного всадника. Это может рассматриваться как реликт ранних космогонических представлений. Появление импортных изделий с изображениями солнца и ...